2006
DOI: 10.1007/bf02758299
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of intranasal midazolam and intravenous diazepam sedation for procedures and seizures

Abstract: Midazolam by the intranasal route provides safe and equally effective non-invasive method of sedation for procedures and seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 7 publications
2
38
0
1
Order By: Relevance
“…Three articles of similar construct compared intranasal midazolam with intravenous diazepam for cessation of seizures rates and time to cessation. [37][38][39] Each research team reached the same conclusions: 1) midazolam injection administered nasally was equally effective as IV diazepam in seizure cessation, and 2) intranasal midazo- lam reduced time to cessation of seizures by eliminating the need to establish IV access. Bhattacharyya et al 40 conducted a controlled trial of intranasal midazolam to rectal diazepam in children.…”
Section: Experience With Intranasal Delivery Of Benzodiazepines For Tmentioning
confidence: 87%
“…Three articles of similar construct compared intranasal midazolam with intravenous diazepam for cessation of seizures rates and time to cessation. [37][38][39] Each research team reached the same conclusions: 1) midazolam injection administered nasally was equally effective as IV diazepam in seizure cessation, and 2) intranasal midazo- lam reduced time to cessation of seizures by eliminating the need to establish IV access. Bhattacharyya et al 40 conducted a controlled trial of intranasal midazolam to rectal diazepam in children.…”
Section: Experience With Intranasal Delivery Of Benzodiazepines For Tmentioning
confidence: 87%
“…Clinical studies on the use of intranasal BDZs for the acute management of seizures are available for MDZ [13][14][15][16][17][18][19][20][21][22] and LZP [23,24] suggesting that, in both cases, the intranasal delivery is a potentially efficient alternative root of administration (Table 3) and ad hoc technologies are currently under investigation. In particular, there are two intranasal DZP formulations currently under development by Neurelis (10 mg) and Acorda Therapeutics (20 mg) and a MDZ intranasal formulation by Upsher-Smith Laboratories (2.5 mg, 5 mg, 7.5 mg) [10].…”
Section: Intranasal Deliverymentioning
confidence: 99%
“…A number of trials compared intranasal MDZ with either rectal DZP or intravenous DZP [13][14][15][16][17][18][19][20][21][22] (Table 3). Available data suggests that intranasal MDZ is effective, safe and more efficient that rectal DZP in controlling seizure activity [7] (Table 3).…”
Section: Intranasal Deliverymentioning
confidence: 99%
“…13 Several authors have also assessed the time to seizure termination with IV vs. alternative routes of medication (intranasal (IN), IM, and buccal). 13,51,53,55,58,59 In general, investigators have shown that while benzodiazepines delivered via an IV have a more rapid onset of action from dose delivery to seizure cessation, a greater amount of time is required to place the IV than to deliver the therapy by non-IV routes. 13,55,59,60,61 Therefore, the total amount of time from the decision to treat with a benzodiazepine to seizure cessation is equivalent or less when alternative routes are used.…”
Section: Therapy: IV Vs Non-iv Treatmentmentioning
confidence: 99%